Analysis of low-frequency vibration-assisted bone drilling in reducing thermal injury. Issue 1 (2nd January 2021) - Chen, Jie; An, Qinglong; Zou, Fan; Yu, Dedong; Chen, Ming
ABSTRACT: Thermal injuries inflicted during bone drilling significantly affect the success rate of surgery, hence, it is important to control thermal injury through temperature reduction. Low-frequency vibration-assisted drilling (LFVAD) is proposed here to reduce thermal injury to bones. Subsequently, the effectiveness of this process is experimentally verified. Based on the trajectories of the cutting edge in LFVAD, the duty ratio and maximum uncut chip thickness are analyzed by varying the amplitude and feed per tooth. A special fixture is designed and the temperature field is measured using an infrared thermography camera. Furthermore, a verification experiment is performed on the machine tool using a low-frequency vibration tool holder. The maximum temperature rise is used to evaluate the drilling temperature, and a thermal injury factor is proposed to evaluate the size of the thermal injury area. Results show that LFVAD effectively reduced thermal injury during bone drilling. The non-cutting effect during LFVAD interrupted the continuous accumulation of cutting heat and promoted the dissipation of cutting heat. Under the experimental parameters used in this study with LFVAD, the maximum temperature rise reduced up to 29.7% and the thermal injury factor reduced up to 18.3%, as compared to those of conventional drilling.